Implementasi Kegiatan Mujāhadah Dan Orientasi Kepesantrenan Dalam Penguatan Karakter Religius Siswa Kelas 6 MI Al Uswah Slogohimo - Bimanyu Bimanyu; Fitri Wahyuni; Arik Dwijayanto (BASICA, 2024)
In response to the declining level of students’ religious character in the digital era, a comprehensive educational approach is required that emphasizes not only cognitive aspects but also spiritual development. This study aims to analyze the implementation of Mujāhadah and Pesantren Orientation programs in strengthening the religious character of sixth-grade students at MI Al Uswah Slogohimo, as well as to identify supporting and inhibiting factors in their implementation. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, direct observation, and documentation involving the principal, teachers, and sixth-grade students as research subjects. The data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the Mujāhadah and Pesantren Orientation activities were implemented regularly and systematically, integrating spiritual practices such as prayer, dzikir, and Qur’anic recitation into students’ daily routines. These activities contributed positively to enhancing students’ religious awareness, discipline, respect toward teachers, and moral conduct. The success of these programs was supported by the commitment of the school, active teacher involvement, and parental support. However, challenges remained, including students’ limited understanding of the essence of the activities and external environmental influences. Overall, the study concludes that pesantren-based religious activities effectively strengthen students’ religious character and serve as a relevant model for Islamic primary education in the modern era.